Code name Arcadia : the first wartime conference of Churchill and Roosevelt - Shortal, John F., 1951- (Williams-Ford Texas A&M University military history series, 2021)
The First Washington Conference, codenamed Arcadia, was a secret meeting held in the days immediately following the entrance of the United States into World War II. It was the first meeting between the United States and Britain to determine military strategy. Franklin Roosevelt, Winston Churchill, and their top military advisors spent hours making major decisions that would determine the direction of the Allied war effort. The main achievement of the conference was the "Europe first" decision, declaring that the defeat of Germany was the highest priority.Neither side knew what to expect before this momentous meeting. Before the war, the British and the Americans had differing strategic concerns, especially about the Pacific and East Asia: differences of such contrast that the conference was in jeopardy of ending early if not resolved. The narrative uses a chronological approach that examines in detail each day of the conference. This day-by-day methodology shows the gradual development of rapport between the allied chieftains, why and how it forged relationships, and the undercurrent of tension as each ally sought to ensure its national interests while cooperating with the other in a grand alliance.Historian and retired Brigadier General John F. Shortal skillfully unravels the inside story of this pivotal meeting. He shows how the working and personal relationships between Roosevelt and Churchill, as well as their military chiefs of staffs, first took root and then blossomed during the conference. Code Name Arcadia makes a major contribution not only to the history of World War II, but also to our understanding of the power structure of the postwar world.